The greenhouse gas balance of Italy : an insight on managed and natural terrestrial ecosystems - Valentini, Riccardo; Miglietta, Franco (Environmental Science and Engineering,, 2015)
The book addresses in a comprehensive way the full greenhouse gases budget of the Italian landscape, focusing on land use and terrestrial ecosystems. In recent years there has been a growing interest in the role of terrestrial ecosystems with regard to the carbon cycle and only recently a regional approach has been considered for its specificity in terms of new methodologies for observations and models and its relevance for national policies on mitigation and adaptation to climate changes. In terms of methods this book describes the role of  flux networks and data-driven models, airborne regional measurements of fluxes and specific sectoral approaches related to important components of the human and natural landscapes. There is also a growing need on the part of institutions, agencies and policy stakeholders for new data and analyses enabling them to improve their national inventories of greenhouse gases and their compliance  with the UNFCCC process. In this respect the data presented is a basis for a full carbon accounting and available to relevant stakeholders for improvements and/or verification of national inventories. The wealth of research information is the result of a national project, CARBOITALY, which involved 15 Italian institutions and several researchers to provide new data and analyses in the framework of climate policies.